Comparative Analysis of Rural Development Strategies in India, Bangladesh, Vietnam, and China: Contextual Lessons for Afghanistan - Fayaz Gul Mazloum Yar; Bashir Ahmad Niazmal (Green Publisher Indonesia, 2025)
Rural development remains a cornerstone of sustainable national growth, particularly in developing and post-conflict nations where rural areas house the majority of the population. This study conducts a comparative analysis of rural development strategies in four countries—India, Bangladesh, Vietnam, and China—that have achieved significant success in reducing rural poverty and fostering socio-economic transformation. Using a mixed-methods approach, the research integrates qualitative analysis of policy frameworks and governance models with quantitative indicators such as rural poverty rates, infrastructure access, and income growth. The findings reveal that those successful strategies hinge on integrated approaches, including decentralized governance (India), community-driven microfinance (Bangladesh), land tenure reforms (Vietnam), and state-led infrastructure investment (China). Common enablers include strong institutional frameworks, targeted poverty alleviation programs, and gender-inclusive policies. For Afghanistan, which faces persistent rural underdevelopment due to conflict, weak institutions, and aid dependency, the study advocates for a hybrid model combining localized governance, NGO partnerships, and conflict-sensitive infrastructure investments. The research contributes to the rural development literature by offering actionable insights for adapting international best practices to fragile states, emphasizing the need for context-specific, equity-focused policies.